2005
DOI: 10.1002/path.1781
|View full text |Cite
|
Sign up to set email alerts
|

IgVH mutations in blastoid mantle cell lymphoma characterize a subgroup with a tendency to more favourable clinical outcome

Abstract: Mantle cell lymphoma (MCL) is associated with a very unfavourable clinical course. This is particularly true for mantle cell lymphoma of the blastoid subtype (MCL-b). In order to define prognostic factors, we analysed the impact of immunoglobulin heavy chain variable (IgV H) gene somatic hypermutations on clinical outcome in a series of 21 cases of morphologically, phenotypically, and genotypically well-characterized MCL-b. Testing and estimation were performed using log-rank statistics and displayed on Kaplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
(37 reference statements)
0
21
0
4
Order By: Relevance
“…The clinical significance of IGVH mutations in MCL is controversial. Most studies have shown no relationship to the outcome of the patients (28)(29)(30), whereas a tendency to longer survival of the hypermutated MCL has been observed in some series (30)(31)(32)(33). Most of these studies have used a cutoff of 2% to consider the tumor as hypermutated.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical significance of IGVH mutations in MCL is controversial. Most studies have shown no relationship to the outcome of the patients (28)(29)(30), whereas a tendency to longer survival of the hypermutated MCL has been observed in some series (30)(31)(32)(33). Most of these studies have used a cutoff of 2% to consider the tumor as hypermutated.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Cases with a homology rate lower than 98% when compared to the closest germ-line IGHVsequence in the IMGT database (https://imgt.cines.fr/) using the IMGT/V-QUEST software were considered mutated. 29 In addition, bone marrow and peripheral blood samples were analyzed in a central laboratory by polymerase chain reaction (PCR) at baseline for the presence of the chromosomal translocation t(11;14)(q13;32) and, in negative cases, for monoclonal IGHV rearrangement, which were to be used as molecular markers during the follow-up. The t(11;14) was evaluated as described elsewhere, 27 while monoclonal IGH rearrangements were assessed using the IGH Gene Clonality Assay targeting the FR3-JH segments (InVivoScribe Technologies, San Diego, CA, USA).…”
Section: Central Pathology Review and Molecular Follow-upmentioning
confidence: 99%
“…[4][5][6] However, unlike in chronic lymphocytic leukemia, in MCL the variable heavy chain gene (VH) mutation status shows no association with ZAP-70 expression and its prognostic relevance is the subject of heated debate. [6][7][8] Additional genetic alterations that occur in subsets of MCL appear to disturb the cell cycle machinery and to interfere with cellular responses to DNA damage. In particular, cyclin D1 upregulation, genomic amplification of cyclin-dependent kinase 4 (CDK4), deletions of the CDK inhibitor p16INK4a, and overexpression of BMI-1, a transcriptional repressor of the p16INK4a locus, are associated with deregulation of cell cycling in MCL.…”
Section: Introductionmentioning
confidence: 99%